New coronavirus and hypothalamic-pituitary-ovarian axis in women: A narrative review - Athar RasekhJahromi; Majid Vatankhah; Mehrdad Malekshoar; Marzieh Haghbeen; Mojtaba Ghaedi; Navid Kalani; Naser Hatami; Seyed Ebrahim Sadeghi (Mashhad University of Medical Sciences, 2022)
Introduction: The COVID-19 epidemic has severely affected the life of people around the world. Periods of stress and psychological distress caused by this pandemic can affect a woman's menstrual cycle. The COVID-19 pandemic has had a significant impact on women's reproductive health. This narrative review was performed with aim to evaluate the effect of coronavirus on different aspects of each part of this axis and its relationship with women's health considering hypothalamic-pituitary-ovarian axis.Methods: In this narrative review study, the databases of Pubmed, Scopus, and Embase were searched using the keywords of "Female Reproductive System", "Hypothalamus", "Pituitary" and "Ovary" with the keywords of "COVID-19" and "SARS-COV-2" with a time limit from 2020 onwards. Then, the studies were summarized conceptually and the findings were categorized and interpreted in terms of the effect of coronavirus on the hypothalamus, pituitary gland, and ovary.Results: The potential neuronal invasion by the coronavirus could had led to its direct effect from the beginning to the end of this axis. Although more studies have examined the effect of COVID-19 on the regulation of sex hormones in women with COVID-19, most studies on the hypothalamic and pituitary axis have been based on genetic simulations.Conclusion: Coronavirus can have a wide impact on all organs involved in the female reproductive system. Over time, our understanding of the possible effects of this disease on female fertility will increase.